If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(x-3)-(6-2x)=2(x+2
We move all terms to the left:
8(x-3)-(6-2x)-(2(x+2)=0
We add all the numbers together, and all the variables
8(x-3)-(-2x+6)-(2(x+2)=0
We multiply parentheses
8x-(-2x+6)-(2(x+2)-24=0
We get rid of parentheses
8x+2x-(2(x+2)-24-6=0
We add all the numbers together, and all the variables
10x-(2(x+2)-24-6=0
| 6(2x+7)-3(x-4)=0 | | 3x-22=4(3-2x) | | .56=n/20 | | .56=x/20 | | 25x-4=40x+5-40x | | 1/2x+3=1/6 | | 2/3=3t/5+2 | | 32x3-98x=0 | | 6-1=7-4y | | 6x-7(x+3=17 | | 3(x-6)^2=48 | | 42000÷x=36 | | (1.15)^x=2 | | x(0.05)+x=1800 | | x(0.05)+x=2900 | | x(0.05)+x=675 | | 10u-5u=10 | | 5x/3+2=6+x | | 4^x=8x | | -9-13f=15-9f | | 49-x+2=10+2x | | 9x-14=6+8x | | 2/3(6x-4)=x+8 | | 4(x−12)+19=-89 | | 11w+4=10w | | 16x²=8x-1 | | 32-x=11 | | 9x²+15x-14=0 | | y2=500 | | 3-(2x+5)=(-x-1)2 | | 4x=50x-4x | | z−1z2=2 |